The Doctrine of Double Effect: An Aid in Decision-Making - Pavol Dancák (Studia Ecologiae et Bioethicae)
Human society of the modern world, which is greatly affected by technological and economic advancements, has to address moral problems with a new urgency. In many instances, the decision does not bring only positive effects. Such cases can be found in applied ethics: bio-medical ethics, business ethics, and legal ethics, but also in other areas of human activity, too, most recently,  in debates, concerning the use of autonomous vehicles or autonomous machines in general. This paper aims to describe and explain the principle of ‘double effect’, when solving complicated and, from the perspective of morality, profoundly dilemmatic situations. The principle of double effect was gradually developed as a means of seeking the right moral decisions. It has a firm and respected position within Catholic medical ethics, but also in secular legislation. The paper presents current thought experiments, which clarify moral decision-making in dilemmatic situations. What seems to be a shortcoming here, is that ethical thought experiments are far too abstract. On the one hand, they refine our knowledge, but on the other hand, they are very partial. The  evolution of medical imaging methods, has enabled us to take a closer look at the relationship between the deontological and utilitarian approaches to making moral judgments, but it does not relieve us of our responsibility for the decisions that we have made. The positive side of the principle of double effect, is that it protects us from the slippery slope of utilitarian consequentialism, where the admission of a lesser evil, is only a step away from committing evil in the name of the greater good.